Characterization of sequence variation in caprine growth hormone gene and its association with milk production traits in two Indian goat breeds - Dixit, Satpal; Sandeep Kumar; Vyas, Manoj Kumar; Singh, M K; Pathodiya, O.P.; Sharma, Anurodh; S Jayakumar (Journal of Livestock Biodiversity, 2025)
Genetic polymorphism in complete caprine growth hormone (GH) gene was investigated by screening 309 DNA samples of both sexes belonging to two Indian goat breeds namely Jamunapari (140) and Sirohi (169) using PCR - single strand conformation polymorphism (SSCP) and DNA sequencing. Twenty four SNPs located in promoter (C160A G164A, T193C), intron 1 (C400T, A497G, G499A and G563A), exon 2 (G781A), exon 3 (G1121A, C1148T, G1170A), intron 3 (G1212T, G1284C), exon 4 (G1442A, A1532G, G1551A, G1578C and C1585T), intron 4 (G1602C), exon 5 (G1938C, G1956C, G2049C, G2058C) and 3 UTR (T2197A) regions were identified. All the identified SNPs were analyzed for the association with different milk production traits. Out of all polymorphic loci analyzed, the SNP located at 781 bp of GH had significant effect on different milk production traits of Sirohi goats. Locus GH_164 and GH_1212 of GH gene were found to be significantly associated with milk production traits in Jamunapari goats. The SNPs at the caprine GH associated with the milk production traits may be used as markers in selection of goats for high milk yield.